Manual ventilation to prevent hypoxaemia during endotracheal intubation of critically ill adults: protocol and statistical analysis plan for a multicentre randomised trial. Issue 8 (10th August 2018) - Casey, Jonathan D; Janz, David R; Russell, Derek W; Vonderhaar, Derek J; Joffe, Aaron M; Dischert, Kevin M; Brown, Ryan M; Lester, Michael G; Zouk, Aline N; Gulati, Swati; Stigler, William S; Rice, Todd W; et al.
Abstract : Introduction: Hypoxaemia is the most common complication during endotracheal intubation of critically ill adults, and it increases the risk of cardiac arrest and death. Manual ventilation between induction and intubation has been hypothesised to decrease the incidence of hypoxaemia, but efficacy and safety data are lacking. Methods and analysis: The Preventing Hypoxemia with Manual Ventilation during Endotracheal Intubation trial is a prospective, multicentre, non-blinded randomised clinical trial being conducted in seven intensive care units in the USA. A total of 400 critically ill adults undergoing endotracheal intubation will be randomised 1:1 to receive prophylactic manual ventilation between induction and endotracheal intubation using a bag-valve-mask device or no prophylactic ventilation. The primary outcome is the lowest arterial oxygen saturation between induction and 2 min after successful endotracheal intubation, which will be analysed as an unadjusted, intention-to-treat comparison of patients randomised to prophylactic ventilation versus patients randomised to no prophylactic ventilation. The secondary outcome is the incidence of severe hypoxaemia, defined as any arterial oxygen saturation of less than 80% between induction and 2 min after endotracheal intubation. Enrolment began on 2 February 2017 and is expected to be complete in May 2018. Ethics and dissemination: The trial was approved by the institutional review boards or designees of all participating centres. The results will be submitted for publication in a peer-reviewed journal and presented at one or more scientific conferences. Trial registration number: NCT03026322 ; Pre-results.